Diamond tools for machining of granite and their wear - Kenda, Jani (Strojniški vestnik, 2009)
The increasing demands of the industry and cultural sculpturing for complex shaped products in natural stone makes the use of flexible and completely automatic machines such as CNC machining centers necessary. These machines mainly use diamond tools such as synthesized diamond mills, circular blades, polishing tools, etc. For the machining of stone, diamond tools are becoming increasingly important and suitable, especially for the machining of granite and other hard stones. The aim of this paper is to present and describe the structure of diamond tools, to present diamond tools for different CNC machining technologies and to characterize the principles of diamond tools wear and forces which are active during the basic type of machining.
Keywords: diamantna orodja; CNC stroji; obraba; sile; diamanti